2019
DOI: 10.1021/acs.jafc.9b06660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hop Bitter Acids, Bitter Components in Beer, on Cognition in Healthy Adults: A Randomized Controlled Trial

Abstract: The present study aimed to investigate the effects of matured hop bitter acids (MHBAs) on human cognition, mental fatigue, and mood state. In this randomized double-blind placebo-controlled study, 60 healthy adults (age 45−64 years) with self-awareness of cognitive decline were randomly divided into 2 groups and received either orally administered MHBAs (35 mg/day) or placebo for 12 weeks. Cognitive functions and mental states were assessed using neuropsychological tests or questionnaires at baseline and weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…MHBAs are also derived from α- and β-acids and show mild bitterness 24 , 25 . In addition, we demonstrated that supplements with MHBAs improve cognitive function, including memory retrieval and attention, in older adults 26 . These findings indicate that activation of the vagus nerve by food ingredients is beneficial for preventing cognitive decline and dementia.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…MHBAs are also derived from α- and β-acids and show mild bitterness 24 , 25 . In addition, we demonstrated that supplements with MHBAs improve cognitive function, including memory retrieval and attention, in older adults 26 . These findings indicate that activation of the vagus nerve by food ingredients is beneficial for preventing cognitive decline and dementia.…”
Section: Introductionmentioning
confidence: 80%
“…Previous studies have shown that MHBAs activate the vagus nerve and increase the levels of noradrenaline, resulting in the improvement of memory impairment 22 . A clinical trial showed that supplements with MHBAs improved cognitive function in older adults with subjective cognitive decline 26 . We have previously shown that MHBAs are associated with the vagus nerve and nicotinic acetylcholine receptors to improve cognitive function 22,23 ; however, the mechanisms underlying the effects of MHBAs on cognitive decline have not been entirely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IAAs exhibit preventive effects on dementia and cognitive decline, which may be mediated by the anti-inflammatory processes driven by PPARγ activation. Previous reports have estimated that reasonable amounts of beer (containing 0.13-1.3 L of IAAs and 0.17-1.8 L of MHBAs) are sufficient to ingest effective doses of these compounds in humans [31,66]. These compounds may contribute to the dementia prevention effects of alcoholic beverages including beer, and it is expected that certain types of beer brewed with a large amount of hops might be more beneficial.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Fukuda et al [66] performed a randomized, double-blind placebo-controlled clinical trial to investigate the effects of MHBAs on human cognitive function. Sixty healthy adults (aged 45-64 years) with insight into their own cognitive decline were randomly divided into two groups and supplemented with MHBAs (35 mg/kg) or placebo for 12 weeks.…”
Section: Mhbas Enhance Cognitive Function Via Activation Of the Vagusmentioning
confidence: 99%
See 1 more Smart Citation